2020
DOI: 10.1111/sms.13690
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of long‐distance running on mechanical and morphological properties of the human plantar fascia

Abstract: Long‐distance running (LDR) can induce transient lowering of the foot arch, which may be associated with mechanical fatigue of the plantar fascia (PF). However, this has not been experimentally tested in vivo. The purpose of this study was to test our hypothesis that LDR induces transient and site‐specific changes in PF stiffness and morphology and that those changes are related to the lowering of the foot arch. Ten male recreational long‐distance runners and 10 untrained men were requested to run overground f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 40 publications
4
23
0
Order By: Relevance
“…No bilateral differences in PF thickness of runners and untrained individuals are consistent with previous findings that PF thickness was not different between recreational runners and untrained individuals 15 , and that PF thickness was not influenced by physical activity 29 . These results, together with our findings, discard the possibility of PF adaptability in terms of its thickness for reducing mechanical stress induced by distance running.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…No bilateral differences in PF thickness of runners and untrained individuals are consistent with previous findings that PF thickness was not different between recreational runners and untrained individuals 15 , and that PF thickness was not influenced by physical activity 29 . These results, together with our findings, discard the possibility of PF adaptability in terms of its thickness for reducing mechanical stress induced by distance running.…”
Section: Discussionsupporting
confidence: 91%
“…The greater load on the left foot during curve running 19 , 20 can induce an increase of mechanical stress on PF. We previously revealed that running causes a decrease in PF SWV at its proximal site 15 , and this coincides with the simulation of stress distribution along PF 11 13 . The bilateral differences in PF stiffness at the proximal site in runners may reflect the adaptation to such stress accumulation in this region of the left foot during track running, regardless of the lateral dominance or foot strike patterns.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Other studies on runners show that an increase in thickness and water content of the plantar fascia was also seen, and that it also caused a reduction in elasticity [19]. Studies on PF also show an increase in thickness of the plantar fascia, which then caused a reduction in plantar fascia elasticity [20][21][22].…”
Section: Introductionmentioning
confidence: 91%